Forskarskolan FRAM - lärare forskar i de främmande språkens didaktik - Bardel, Camilla; Erickson, Gudrun; Granfeldt, Jonas; Rosén, Christina (Language and Literature in Education, 2021)
In recent years, several investments have been made in graduate schools for teachers, with the aim of building up the school's knowledge base and increasing the number of teachers in the school with postgraduate education. The content of this book is based on the results from the national graduate school for language teachers The didactics of foreign languages ​​(FRAM) which was conducted with support from the Swedish Research Council during the period 2012-2015. The graduate school enabled a unique exchange of knowledge between active teachers who found interesting study objects in their current teaching context and the academy's researchers who saw the relevance of the project ideas in the background of the research field. This type of collaboration in research and education fulfilled the overall purpose of the graduate school. A synergy effect was that language didactic research in Sweden received an important addition of classroom-related research projects in a wide range of specializations. Based on the graduate school's three main areas, namely language learning, digital resources in language teaching and language assessment, projects were carved out on multilingualism, motivation, language and subject-integrated teaching, feedback, (co) assessment and much more. Participating authors are ten teachers who have researched the learning, teaching and assessment of English and modern languages. Their work is presented in separate chapters. In the introduction, the book's editors provide an insight into how a graduate school for teachers can be set up and how FRAM has contributed to the expanding and multifaceted research field Language Didactics.